Thermo-Mechanical Properties of Polypropylene Composites Filled with Recycled Office Waste Paper - Cioffi, Marina Gil Almeida [UNESP]; Oliveira, Daniel Magalhaes de [UNESP]; Bomfim, Anne Shayene Campos de [UNESP]; Benini, Kelly Cristina Coelho de Carvalho [UNESP]; Cioffi, Maria Odila Hilario [UNESP]; Voorwald, Herman Jacobus Cornelis[UNESP] (Taylor & Francis Inc, 2022)
The high production of paper, followed by a more significant concern with environmental and economic issues, has led to greater relevance to paper recycling and its raw uses as composite filler. Composites of polypropylene with 10, 20, and 30 wt.% of recycled office waste paper were produced by injection molding and characterized by mechanical and thermal properties. All composites presented a slight reduction of 15 degrees C in thermal stability compared to the polymeric matrix. Moreover, as the filler amount increased, the degree of crystallinity was reduced proportionally. The mechanical test showed similar tensile strength values among neat polymer andcomposites but also showed an increase in the composite's tensile modulus, related to the stiffness of the natural filler. The composite with a higher percentage of waste paper (30 wt.%) maintained equivalent properties as neatpolypropylene and other composites (10 and 20 wt.%). Thus, 30 wt.% composites proved to be an excellent material with less synthetic polymer percentage, keeping thermal and mechanical properties comparable to the neat PP.Furthermore, this composite does not need chemical treatment or additives harmful to the environment. It is suitable for future applications in various plastic products such as packaging and domestic utensils.
Keywords: Waste paper; Polypropylene; Composite; Recycling; Thermal properties; Mechanical properties